Jakob Lothe, Beatrice Sandberg, and Ronald Speirs, eds. Franz Kafka: Narration, Rhetoric, and Reading. Columbus: Ohio State UP, 2011. x + 251 pp. - Richard T Gray (Studies in 20th & 21st Century Literature, 2014)
Review of Jakob Lothe, Beatrice Sandberg, and Ronald Speirs, eds. Franz Kafka: Narration, Rhetoric, and Reading. Columbus: Ohio State UP, 2011. x + 251 pp.
Keywords: Kafka; narration; rhetoric